A Roadmap for Noninvasive Vascular Laboratory Education. Issue 1 (March 2020) - Chou, Daisy; Go, Michael R.; Starr, Jean E.; Satiani, Bhagwan
Since 2014, the Registered Physician in Vascular Interpretation (RPVI) designation has been required for a vascular surgery board certification candidate to register for the vascular surgery certifying exam. Although the importance of the noninvasive vascular laboratory (NIVL) is recognized, vascular laboratory education within vascular surgery fellowship programs is heterogeneous and much less regulated compared with clinical education. Evidence suggests that many vascular surgery trainees may not have received ideal training to obtain RPVI certification or direct an NIVL. The NIVL curriculum at The Ohio State University Wexner Medical Center has been used since 2005 and combines didactics, supervised reading, videos, hands-on experience with vascular sonographers, and one on one time with the vascular laboratory medical director. This curriculum is outlined in this article and can be used as a guide for creating NIVL curricula for vascular surgery and other training programs.